2014
DOI: 10.1002/ppap.201300152
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Activity of Melt Processed Poly(propylene) Ag and Cu Nanocomposites by Argon Plasma Treatment

Abstract: Argon surface plasma treatment (APT) of poly(propylene)/silver (PP/Ag) and poly(propylene)/ copper (PP/Cu) nanocomposite improves their antibacterial properties against pathogenic bacteria. Dispersions of PP/Ag and PP/Cu nanocomposites were prepared by sonication assisted melt mixing 0.05, 0.5, and 5 w/w% metal nanoparticle/polymer compositions, and then melt casted to form films that were surface treated with argon plasma. Scanning electron and atomic force microscopy showed that APT increase the surface roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
2
28
0
2
Order By: Relevance
“…The CNPs were first sonicated in a glass reactor, to induce the deagglomeration of these carbon nanoparticles [34][35][36], as follows: 1 g of CNPs (CNFs and GPs, as well as the CNFs : GPs mixtures, in the following ratios by weight: 9 : 1, 8 : 2, or 7 : 3) was introduced in a glass reactor arranged with a sonotrode (see Figure 1) and sonicated at 20 kHz for 30 min in an air atmosphere. To improve the efficiency of functionalization, magnetic agitation was included.…”
Section: Methodsmentioning
confidence: 99%
“…The CNPs were first sonicated in a glass reactor, to induce the deagglomeration of these carbon nanoparticles [34][35][36], as follows: 1 g of CNPs (CNFs and GPs, as well as the CNFs : GPs mixtures, in the following ratios by weight: 9 : 1, 8 : 2, or 7 : 3) was introduced in a glass reactor arranged with a sonotrode (see Figure 1) and sonicated at 20 kHz for 30 min in an air atmosphere. To improve the efficiency of functionalization, magnetic agitation was included.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is important to find out novel strategies and develop new antimicrobial agent by easy, fast, and environment‐friendly route with a broad‐spectrum of antimicrobial activity . Progress in the research continues, which has produced different organic and inorganic nanomaterials for their bio‐ and medicinal applications . However, most of the nanostructured (NS) thin films are not suitable for antimicrobial and antiviral studies.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the NS metal films like Cu, Ag, Ti, and Au have been reported to have good antibacterial behaviors. Further, the cost‐effectiveness and the easy accessibility of Cu has made it a better option to work with, since it shares characteristic properties similar to those of expensive Ag, Au, and other noble metals. Additionally, NS Cu films have shown antimicrobial activity against a number of bacteria and fungi .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported the treatment of polypropylene PP/Ag and PP/Cu nanocomposites surface by using the argon plasma [41]. They showed that the nanocomposites have a higher quality in the antibacterial efficiency versus, pathogenic, the human disease bacteria, because of the larger surface area of the metal nanoparticles and the raising of the hydrophilicity and the roughness of film surface.…”
mentioning
confidence: 99%